Strain-Level Differentiation of Bacteria by Paper Spray Ionization Mass Spectrometry - Chamberlain, Casey A. (Anal Chem, 2019)
Paper spray ionization-mass spectrometry (PSI-MS) is a relatively new analytical technique allowing for rapid mass spectrometric analysis of biological samples with little or no sample preparation. The expeditious nature of the analysis and minimal requirement for sample preparation makes PSI-MS a promising avenue for future clinical assays with one potential application in the identification of different types of bacteria. Although past PSI-MS studies have demonstrated the ability to distinguish between bacteria of different species and morphological classes, achieving within-species strain-level differentiation has never been performed. In this report, we demonstrate the first strain-level bacterial differentiation by PSI-MS with the mammalian intestinal bacterium Oxalobacter formigenes (Oxf). This novel application holds promising clinical significance as it could be used to differentiate between pathogenic bacteria and their harmless commensal relatives, saving time and money in clinical diagnostics. Both whole cells and cell lysates of Oxalobacter strains HC1 and OxWR were analyzed using the Prosolia Velox™ 360 PSI source coupled to a Thermo Scientific Q Exactive high-resolution mass spectrometer with a rapid 30-sec analytical method. Multivariate statistical analysis followed by examination of significant features provided for and confirmed differentiation between HC1 and OxWR. We report a panel of strain-exclusive metabolites that could serve as potential strain-indicating biomarkers.